2023
DOI: 10.1021/acs.jpclett.3c01038
|View full text |Cite
|
Sign up to set email alerts
|

Torsional Disorder, Symmetry Breaking, and the Crystal Violet Shoulder Controversy

Abstract: The nature of the lowest-energy electronic absorption band of crystal violet (CV) and particularly the origin of its high-energy shoulder have been debated since the middle of the past century. The most recent studies invoke a splitting of the S1 state upon symmetry breaking induced by interactions with the solvent and/or the counterion. Using a combination of stationary and time-resolved polarized spectroscopy together with quantum-chemical calculations, we show that torsional disorder in the ground-state res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 34 publications
0
10
2
Order By: Relevance
“…Additionally, our analysis demonstrates that the dominant factor responsible for the symmetry breaking of CV and the resulting splitting of S 1 and S 2 peaks in methanol is the non-covalent interaction between the CV and the solvent environment rather than torsional disorder, in contrast to the results presented in a recent study. 8 In nonpolar solvents, we find that CV preferentially forms a contact ion configuration with Cl − , leading to strong symmetry breaking and a substantially larger S 1 -S 2 splitting than in methanol. Interestingly, our results demonstrate that the chromophore-ion configurations sampled during the MD in toluene, where the Cl − is preferentially located equidistant between two N atoms, are qualitatively different to the configurations sampled in vacuum, where the Cl − is more preferentially associated with a single N .…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…Additionally, our analysis demonstrates that the dominant factor responsible for the symmetry breaking of CV and the resulting splitting of S 1 and S 2 peaks in methanol is the non-covalent interaction between the CV and the solvent environment rather than torsional disorder, in contrast to the results presented in a recent study. 8 In nonpolar solvents, we find that CV preferentially forms a contact ion configuration with Cl − , leading to strong symmetry breaking and a substantially larger S 1 -S 2 splitting than in methanol. Interestingly, our results demonstrate that the chromophore-ion configurations sampled during the MD in toluene, where the Cl − is preferentially located equidistant between two N atoms, are qualitatively different to the configurations sampled in vacuum, where the Cl − is more preferentially associated with a single N .…”
Section: Discussionmentioning
confidence: 74%
“…4 demonstrate that the S 1 -S 2 peak splitting of the absorption spectrum of CV in methanol is largely driven by symmetry breaking induced through electrostatic interactions with the polar solvent environment around the molecule, rather than symmetry breaking due to solvent-induced slow chromophore motion driven by the twisting of the aryl rings, in contrast with the results presented in a recent study. 8…”
Section: B the Absorption Spectrum Of CV In Methanolmentioning
confidence: 99%
See 2 more Smart Citations
“…Brilliant green showed the absorption maximum at 624 nm, with a sharp decrease in peak intensity within 2 h. Crystal violet shows the main absorption peak with a high-energy shoulder peak between 550 and 600 nm. 51 , 52 A sharp decrease in the intensity of the peak maxima after 2 h was observed. The interfacial interaction of crystal violet at the silica–water interface was measured in real time, 53 which suggested that CV can behave in the solution in two ways.…”
Section: Resultsmentioning
confidence: 89%